Frequency Reuse for Coexistence of Secondary Users and Optimum Utilization of Bandwidth - Annapurna, K.; CK, Meghalatha; Seetha Ramanjaneyulu, B. (International Journal of Engineering and Technology, 2018)
Cognitive radio technology is a promising technology to address the spectrum underutilization of licensed users, called primary users and extreme requirement of unlicensed users, called secondary users. Day to day spectrum requirement of secondary users is being increased dramatically and results in increased blocking and dropping. Call dropping is more exasperating than call blocking. So to reduce the call dropping of secondary users, some of the researchers proposed channel reservation techniques. But they got improved dropping results at the cost of increased blocking. So frequency reuse is proposed in this paper, which improves both blocking and dropping.